Sequence-Related Amplified Polymorphism (SRAP) analysis for studying genetic characterization of Bouea macrophylla - SOMBHAT KAEWPONGUMPAI; SUPATTRA POEAIM; ONGKARN VANIJAJIVA (Biodiversitas Journal of Biological Diversity, 2016)
Kaewpongumpai S, Poeaim S, Vanijajiva O. 2016. Sequence-Related Amplified Polymorphism (SRAP) analysis for studying genetic characterization of Bouea macrophylla. Biodiversitas 17: 539-543. Bouea macrophylla Griff. is well-known as one of native typical fruits in Southeast Asia which needs to be preserved and continuously cultivated because of economical and ecological significances. More recently, sequence-related amplified polymorphism (SRAP) markers have been developed, which are used to amplify coding regions of DNA with primers targeting open reading frames. This technique has proven to be robust and highly variable and is attained through a significantly less technically demanding process. In this research, SRAP method was preliminary applied to assess genetic characterization of B. macrophylla. Genomic DNA was extracted from fresh leaf samples. The result clearly showed that at 100 ng template DNA and MgCl2 5 mM concentration are suitable for further PCR analysis. Thirty SRAP primer combinations were initially screened for analysis and 26 primer combinations were chosen for further analysis. A total of 222 DNA fragments, varying from 90-2500 bp, were amplified. The produced band number for each optimal primer set ranged from 3 to 12 with a percentage of polymorphic bands spanning from 33.33 to 80.00%. Therefore, SRAP analysis is suitable for further analysis method on genetic study of Bouea species and related genera.